KUALITAS PELAYANAN PUBLIK DI PEMERINTAH DESA ENTALSEWU KECAMATAN BUDURAN KABUPATEN SIDOARJO - Vicky Pra Styo; Hendra Sukmana (Universitas Bina Taruna Gorontalo, 2022)
The purpose of the study was to analyze and describe the quality of public services in the Entalsewu Village Government, Buduran District, Sidoarjo Regency. The research method was carried out qualitatively with a case study approach. Collecting data by interview, observation and documentation. Data processing with reduction, data presentation and conclusion drawing. The validity of the data with credibility test through triangulation of sources and techniques. The results showed: (1) the ability of human resources: first, skilled in compiling and storing public service files. Second, have a good knowledge of filing and administering services. Third, have a disciplined attitude to work, friendly and fair in service. (2) the facilities and infrastructure used: computers, handtrees, filing cabinets, waiting rooms. (3) service procedures: starting from the head of the neighborhood unit or residents, continued at the village office and other government offices (4) types of public services, namely the management of police records, certificates of inability to education and health, management of loss, birth management, death management, marriage management, business domicile management, business license information processing, moving location management, travel management, people's business credit management, management of decreasing or adding electricity power and managing different names.